Life cycle assessment of nanoalloy enhanced layered perovskite solid-solid phase change material till 10000 thermal cycles for energy storage applications. (March 2021) - Raj, Cyril Reuben; Suresh, S.; Singh, Vivek Kumar; Bhavsar, R.R.; Chandrasekar, M.; Archita, V.
Highlights: Nano gallium/indium eutectic alloy capsule by in-situ polymerization with UF shell. SS-PCM with n-LMA additive (5wt.%) was used to study thermal performance. Latent heat and thermal conductivity of SS-PCM/n-LMA increased by 17.61% and 21.05%. SS-PCM/n-LMA attains physical, chemical, thermal stability upto 10000 cycles. Nano LMA enhanced SS-PCM with higher stability for thermal energy storage system Abstract: Advancement in thermal energy management systems especially in Green building, Electronic/Avionic system, Thermal comfort clothing, Storage for Food and Medical utilities requires sophisticated mechanisms to maintain constant temperature for prolonged period. Phase Change Material (PCM) based thermal energy storage systems act as an effective resource but lags in retaining its performance for longer duration. This article illustrates a synthesised manganese based layered perovskite Solid-Solid PCM (SS-PCM) homogenized with 5 wt.% of nano-encapsulated liquid gallium-indium metal alloy (n-LMA), for energy storage applications by virtue of its high physical, chemical and thermal stability, enhanced thermal conductivity and latent enthalpy. Life cycle assessment of the prepared SS-PCM/n-LMA was conducted using a thermal cycling chamber for 1000, 4000, 7000, and 10000 thermal cycles. Thermal-cycled SS-PCM/n-LMA was characterized for its nano-structural morphology, elemental and chemical composition, thermo-physical properties including phase transition behaviour, enthalpy, thermal degradation, specific heat capacity, and thermal conductivity through FESEM, TEM, SEM, EDS, FTIR, DSC, TGA, and LFA. Addition of n-LMA exhibited an enhancement in thermal conductivity of 21.05% (0.374 W/m-K); charging-discharging enthalpy of 16.84% (74.56 J/g) and 17.61% (76.32 J/g) respectively and increases the energy storage performance. However, effect of thermal cycling led to slight reduction in latent heat by 13.26% (charging), and 12.95% (discharging); and thermal conductivity by 9.15%. The results concluded that SS-PCM/n-LMA composite was highly stable, satisfying physical, chemical and thermal stability till 10000 thermal cycles which ensures its suitability for long-term energy storage applications. Graphical Abstract: Image, graphical abstract